Leader similarity and international sanctions - Jerg Gutmann; Pascal Langer; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
Political leaders matter, but statistical evidence for their relevance in international politics is scarce. We estimate panel probit models with data for the period 1970 to 2004 and sender-year and dyad fixed effects to evaluate whether more similar leaders are less likely to sanction each other. We find that higher leader similarity significantly reduces the likelihood of sanction imposition. The effect is especially pronounced when UN and EU sanctions are excluded, that is, when focusing on sanctions imposed through unilateral political decisions. In this case, going from no correlation to perfect correlation in the characteristics of the leader pair lowers the likelihood of sanctions by 5.7 pp. Moreover, leader similarity seems to matter especially for sanctions aimed at democratic change or human rights improvements, where political leaders are expected to enjoy more discretion.
Keywords: D70; F51; K33; 330; International sanctions; Leader similarity; Political leaders